Gandhi and King the power of nonviolent resistance - Nojeim, Michael J. (Praeger, 2004)
"The lives and works of Mohandis Karamchand Gandhi and Martin Luther King Jr. have much to teach us about nonviolent resistance to oppression. This book presents a comparative analysis of their legacies that demonstrates how powerful peace and love can be, even in the face of hate-filled oppression, aggression, and violence." "No two individuals had a greater impact on the 20th century's monumental struggles for freedom, justice, and peace. Gandhi showed the world that steadfastly and nonviolently adhering to the truth gave the world a practical alternative to the madness of war and violence. King used nonviolence to realize his dream of a beloved community and to beckon his white countrymen to live up to the lofty ideals bequeathed to them by America's founders. The two men came from widely divergent cultural, religious, economic, and political backgrounds and settings, yet they both wielded nonviolent weapons effectively. This comparison not only demonstrates the broad applicability of nonviolent principles, but also highlights the importance of merging high ideals with a practical program that produces positive results in people's lives."--BOOK JACKET.